Turn-Taking Strategies Used by Lincoln-Douglas Debate Final Round 2019 - Febryanto, Mohammad; Puspita Rizki, Nadya (Jurnal Bahasa Inggris Terapan, 2023)
This study aims to find out what kinds of turn-taking strategies are used in Lincoln-Douglas debate final round between Nehal Chigurupati as the affirmative speaker and Grace Johannes as the negative speaker. This study has two purposes: the first is to find out what kinds of turn-taking strategies are used by the Lincoln-Douglas debate, and the second is to find out the most dominant type of turn-taking strategies used by the Lincoln-Douglas final debate. A descriptive qualitative method was used in this study while Stenstrom’s (1994) theory was applied to analyze the data. The results show that 31 data were found which consist of taking the turn strategies (16), holding the turn (10), and yielding the turn (5). The findings imply that the most dominant strategy used by the Lincoln-Douglas debate is turn-taking strategies